The Effectiveness of Honey in Physiological Nacl to Maintain of Viability and Motility of Spermatozoa - Agustina, Elsa; Hermadi, Herry Agoes; S, Hario Puntodewo; Hernawati, Tatik; Triana, Indah Norma; Safitri, Erma (KnE Life Sciences, 2017)
This research was conducted to determine whether there is influence of various concentrations of mead physiological saline as diluent on the viability and motility fat-tailed sheep during storage 5°C. This research is compiled using the trial completely randomized design (CRD). Differences in the treatment of thinning the honey in physiological saline are PO (0%), P1 (0.2%), P2 (0.4%), P3 (0.6%), P4 (0.8%). The treatment stored in a refrigerator at a temperature of 5°C and then observed every 0, 24, and 48 hours. Data were analyzed by ANOVA followed by Duncan's Multiple Range Test. The conclusions obtained from this research there is the effect of adding various concentrations of NaCl physiological mead on the viability and motility fat tailed sheep during storage 5°C and consentration mead NaCl physiological to maintain viability and motility best tail sheep are treated P3 (0.6% solution = 0.6 ml honey in 99.4 ml physiological NaCl) at the time T24 (24 hours). Key words: Fat-Tailed Sheep, Honey, Motility, Physiological NaCl, Spermatozoa, Viability